PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SD 3 PAPRINGAN - Indah Munawaroh; Amalia Rahmawati; Deki Wibowo; Septina Rahmawati; Yoga Awalludin Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect and differences before and after applying the discovery learning model on student learning outcomes in IPAS (Integrated Science) for fourth-grade elementary school students. The research employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The population consisted of 49 students divided into two classes, namely 24 students of grade IV SD 3 Papringan as the experimental class and 25 students of grade IV SD 2 Papringan as the control class. Data were collected through observation, interviews, tests, and documentation. The test instruments were examined for validity, reliability, difficulty level, and discriminating power, resulting in 20 valid items used in the pretest and posttest. Data analysis included normality test, homogeneity test, independent sample t-test, and paired sample t-test. The results of the independent sample t-test showed a significance value (2-tailed) = 0.030 < 0.05, indicating a significant effect of the discovery learning model compared to conventional learning. Meanwhile, the paired sample t-test produced a significance value (2-tailed) = 0.000 < 0.05, confirming a significant improvement in student learning outcomes after the implementation of discovery learning. These findings suggest that discovery learning is effective in enhancing both academic achievement and active participation in the learning process.